Disruption, Discovery, and Field Courses: A Case Study of Student Engagement during a Global Pandemic. Issue 1 (2nd January 2022) - Gibbes, Cerian; Skop, Emily
Abstract : This article examines the impact of the COVID-19 pandemic on the teaching of a geography field course. What was discovered from the teaching of a geography field course using a remote learning structure? To answer this, we reflect on the adaptation of an Urban Sustainability field course taught during the COVID-19 pandemic. Framed by the pedagogical context for engaging in field courses, we define what experiential learning looks like within a remote learning structure. This new approach to teaching challenged our assumptions about how students engage with the world. In this article we share lessons learned about the adaptability of experiential learning opportunities. We conclude with a discussion of the global pandemic as a difficult yet opportune time to disrupt and experiment with new forms of teaching. Although the pandemic restricted human interaction, we reveal different types of connections and ways to engage with the field. Through a discussion of the impact of the global pandemic on the signature feature of geographers' work—fieldwork—this article contributes to the evolving roles of the professional geographer in the twenty-first century.